Quasi-Steady Analytical Model Benchmark of an Impulse Turbine for Wave Energy Extraction - A. Thakker; J. Jarvis; A. Sahed (International Journal of Rotating Machinery)
This work presents a mean line analysis for the prediction of the performance and aerodynamic loss of axial flow impulse turbine wave energy extraction, which can be easily incorporated into the turbine design program. The model is based on the momentum principle and the well-known Euler turbine equation. Predictions of torque, pressure drop, and turbine efficiency showed favorable agreement with experimental results. The variation of the flow incidence and exit angles with the flow coefficient has been reported for the first time in the field of wave energy extraction. Furthermore, an optimum range of upstream guide vanes setting up angle was determined, which optimized the impulse turbine performance prediction under movable guide vanes working condition.